2014
DOI: 10.1210/jc.2013-3507
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Is Associated With Inflammation in Older Irish Adults

Abstract: This study demonstrated significant associations between low vitamin D status and markers of inflammation (including the ratio of IL-6 to IL-10) within elderly adults. These findings suggest that an adequate vitamin D status may be required for optimal immune function, particularly within the older adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(136 citation statements)
references
References 51 publications
11
123
0
2
Order By: Relevance
“…Our findings are of importance because little it is known about the relationship between 25(OH)D levels and immune markers of inflammation, especially in the elderly. The few published data coming from observational studies (Amer and Qayyum 2012;Reyman et al 2013;Laird et al 2014;Ngo et al 2010;Peterson and Heffernan 2008) support a primary anti-inflammatory role of vitamin D. In a very recent observational investigation conducted in 957 older Irish adults (>60 years of age), Laird et al (Laird et al 2014) showed a significant association between low vitamin D status (25OH-D <25 nmol/L) and markers of inflammation including IL-6, TNF-α, IL-10, hsCRP, and the ratio of IL-6 to IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are of importance because little it is known about the relationship between 25(OH)D levels and immune markers of inflammation, especially in the elderly. The few published data coming from observational studies (Amer and Qayyum 2012;Reyman et al 2013;Laird et al 2014;Ngo et al 2010;Peterson and Heffernan 2008) support a primary anti-inflammatory role of vitamin D. In a very recent observational investigation conducted in 957 older Irish adults (>60 years of age), Laird et al (Laird et al 2014) showed a significant association between low vitamin D status (25OH-D <25 nmol/L) and markers of inflammation including IL-6, TNF-α, IL-10, hsCRP, and the ratio of IL-6 to IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of biologically plausible mechanisms may mediate the hepato-protective role for the active metabolite of vitamin D 3 . 1,25-dihydroxyvitamin D 3 modulates the insulin signaling pathway/IR, suppresses fibroblast proliferation and collagen production, exerts profibrinolytic effects, and modulates macrophage activity and inflammatory cytokine generation (e.g., TNF-alpha, interleukin-6, and other cytokines) [27,57,60,63,64]. Thus, vitamin D 3 deficiency or insufficiency should be ruled out in future studies assessing the association between NAFLD and BMD.…”
Section: Low Bone Mineral Density (Osteoporosis/osteomalacia)mentioning
confidence: 99%
“…It has been reported that vitamin D could play a key role in immune activation and inflammation [6,7]. Moreover, vitamin D can prevent the destruction of pancreatic betacells and reduce the incidence of diabetes mellitus, possibly secondary to inhibition of proinflammatory cytokines [8][9][10].…”
Section: Introductionmentioning
confidence: 99%